Supply Chain Analysis A Handbook on the Interaction of Information, System and Optimization - Tang, Christopher S.; Teo, Chung-Piaw.; Wei, Kwok-Kee.; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
SUPPLY CHAIN ANALYSIS: A Handbook on the Interaction of Information, System, and Optimization is a carefully developed work focused on the analysis of supply chain interaction issues in emerging markets and industry sectors. It is a leading-edge handbook that will emphasize where little work has been done and where the "rubber meets the road" $1 (Bthe supply chain process, information, and systems integration. These are pertinent issues facing practitioners and researchers in today$1 (Bs business environment. This is a gap-bridging handbook that analyzes interaction issues from both the research and practitioner sides. The result is a volume that examines and provides practical solutions on interaction issues while being firmly grounded in research principles. Some of the topical areas the Handbook examines are: The issue of supply chain design, from the perspective of foreign cosmetic companies in China; The issue of supply chain coordination among the grocery manufacturers. Most notably, the opportunity for strategic, multi-lateral collaboration through a shared distribution network; The impact of online secondary markets on the operational issues of a supply chain; The critical importance of risk and disruption in supply chain; and the huge issue of integrating demand and supply, hence the need to synchronize the supply chain with the demand chain.s
Supply Chain Configurations of Foreign Cosmetics Companies Operating in China -- Structural Supply Chain Collaboration Among Grocery Manufacturers -- Supply Chain Management in the Chemical Industry: Trends, Issues, and Research Interests -- Berth Allocation Planning Optimization in Container Terminals -- Merchandise Planning Models for Fashion Retailing -- Supply Chain Management in the Presence of Secondary Market -- Global Diffusion of ISO 9000 Certification Through Supply Chains -- Risk Management in Global Supply Chain Networks -- Trust and Power Influences in Supply Chain Collaboration -- Foreign Direct Investment or Outsourcing: A Tax Integrated Supply Chain Decision Model -- Integrating Demand and Supply Chains -- Mumbai Tiffin (Dabba) Express.
Keywords: Business; Management science; Production management; Operations research; Decision making; Information technology; Business -- Data processing; Industrial engineering; Production engineering; Engineering economics; Engineering economy; Business and Management; Operations Management; Engineering Economics, Organization, Logistics, Marketing; IT in Business; Operation Research/Decision Theory; Industrial and Production Engineering; Business and Management, general; Electronic books